HUKUM INTERNASIONAL SEBAGAI SUMBER HUKUM DALAM HUKUM NASIONAL (Dalam Perspektif Hubungan Hukum Internasional Dan Hukum Nasional Di Indonesia) - Dina Sunyowati (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Countries agreement contained in an international agreement in the form of bilateral agreements, regional and multilateral agreements that are binding on the parties and a law for that entered into an agreement (pacta sunt servanda). International agreements that have been agreed and validated in a ratification by a country, then the agreement is valid and binding upon all be a source of law for the enforcement of law in making decisions. This is true also in Indonesia. Any international agreement that has been followed by Indonesia, which is contained in a ratification requirement or not, still have the force of binding for both parties. Keywords: International Law, Sources of Law, International Treaties, International Agreements.